2022
DOI: 10.3390/su15010038
|View full text |Cite
|
Sign up to set email alerts
|

Explore U.S. Retailers’ Sourcing Strategies for Clothing Made from Recycled Textile Materials

Abstract: This study explored U.S. retailers’ sourcing patterns for clothing made from recycled textile materials. Based on a statistical analysis of over 3000 such clothing items for sale in the U.S. retail market from January 2019 to August 2022 at the Stock Keeping Unit (SKU) level, the study found that U.S. retailers adopted a diverse sourcing base for clothing made from recycled textile materials, covering developed and developing economies worldwide. Additionally, an exporting country’s economic development level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Specifically, according to the factor proportion trade theory, countries should specialize in producing goods that intensively use their abundant production factors, such as labor and capital [18]. In general, developing countries abundant with cheap labor are typically involved in making labor-intensive products, whereas developed countries, rich in capital and technology, generally focus on making capital and technology-intensive goods [19,20].…”
Section: Literature Review 21 Supply Chains For Making Clothing Using...mentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, according to the factor proportion trade theory, countries should specialize in producing goods that intensively use their abundant production factors, such as labor and capital [18]. In general, developing countries abundant with cheap labor are typically involved in making labor-intensive products, whereas developed countries, rich in capital and technology, generally focus on making capital and technology-intensive goods [19,20].…”
Section: Literature Review 21 Supply Chains For Making Clothing Using...mentioning
confidence: 99%
“…However, companies usually rely on expensive and specialized machinery to mechanically or chemically transform sorted textile waste into recycled fibers and further process them into new yarns and fabrics [22]. Further, studies found that cutting and sewing recycled fabrics into clothing is not significantly different from making clothing using virgin fibers, and it remains a labor-intensive process [20,23].…”
Section: Literature Review 21 Supply Chains For Making Clothing Using...mentioning
confidence: 99%
See 3 more Smart Citations